Madrasah, Quality and Strategic Plan - Abu Darda (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
This paper aims to understand the the quality improvement of Madrasah as one of the Islamic education institutions of Indonesia, through the construction of strategic plan (renstra) for the development of Islamic education. Madrasah quality must be well managed so that it can realize the goals and noble values of Islamic education. Its missions are actually heavier than public schools because of the broader range of functions and tasks. Its goal as Islamic education institutions includes spiritual competence, religious character, in addition to social, personal, academic and vocational competencies. This paper finds out that managerial stages to improve the quality of madrasah are: inventory of main activities; strategy formulation; action plan and scheme of procedure for developing quality learning. According to the experience of KMI Pondok Modern Darussalam Gontor in the construction of the Science and Technology development strategic plan, it involves some actions, such as: To formulate a strategy; describe real challenges; goal achievement strategy; target and size for each strategy; SWOT analysis; alternative steps for solving; action plan and implementation program; and schedule of activities. The strategic objectives, including the following: curriculum and learning process; madrasah leadership and management; organization and institutions; workforce; financing and funding; learners; the role of the community; madrasah environment and culture.